Antidiabetic effect of a black mangrove species Aegiceras corniculatum in alloxan-induced diabetic rats - S Gurudeeban; K Satyavani; T Ramanathan; T Balasubramanian (Wolters Kluwer Medknow Publications, 2012)
Earlier ethnopharmacological records divulged the traditional usages of mangrove Aegiceras corniculatum (Linn.) Blanco distributed in coastal and estuarine areas of Southeast India. Excluding scientific knowledge of A. corniculatum against diabetes an upgrowing endocrinal disorder, our present study evaluated the effect on alloxan-induced diabetic rats. Diabetes was induced in adult rats of the Wistar strain by intraperitoneal injection of alloxan monohydrate. The experimental rats were administered with leaf suspension of A. corniculatum post orally using an intragastric tube. On completion of the 60-day treatment, a range of biochemical parameters were tested including liver hexokinase, glucose-6phosphatase and fructose 1, 6 bisphosphatase in the liver of control and allaxon-diabetic rats. As a result, A. corniculatum leaf suspension showed moderate reduction in blood glucose (from 382 ± 34 to 105 ± 35), glycosylated hemoglobin, a decrease in the activities of glucose-6 phosphatase and fructose 1, 6-bisphosphatase, and an increase activity of liver hexokinase achieved through the oral administration of extract on 100 mg/kg. The present findings support promising results in terms of antidiabetic activities establishing its candidacy for further purification of individual compound in order to understand their mechanism of action.